Immunophenotypic criteria for the diagnosis of non-Hodgkin's lymphoma. - Picker, L. J. (1987)
This study examines the immunohistologic profiles of a large series of histologically proven benign and malignant lymphoproliferative processes in order to define immunophenotypic criteria useful in the diagnosis of non-Hodgkin's lymphoma. Using a method of analysis relying solely on immunoarchitectural features of a given case, the authors were able to define immunologic criteria capable of differentiating benign from malignant lymphoid processes independent from conventional morphologic analysis. In general, these criteria involved identification of abnormal expression or loss of antigens in B- and T-lineage populations. Among B-lineage populations the following features were associated with malignant histology: 1) light-chain-restricted B lineage, 2) light chain -B lineage, 3) Leu-1+ B lineage, 4) L60+ B lineage, 5) 41H+, Ki-67+ B lineage, 6) loss of pan-B antigens, and 7) LFA-1-B lineage. Among T-cell populations outside the thymus, phenotypes associated with malignancy included 1) loss of pan-T antigens (including loss of the beta chain of the T-cell antigen receptor), 2) coexpression or loss of T-subset antigens, 3) Leu-6+ T-lineage, and 4) MB-1+ T lineage. Application of these criteria to a series of nearly 500 cases of lymphoma indicated that over 90% of B-lineage and about 80% of T-lineage neoplasms manifested immunophenotypic abnormalities that could distinguish them from benign, reactive lymphoid processes. It is concluded that immunophenotypic analysis of lymphoproliferative lesions is sufficiently sensitive and specific to confirm the histologic diagnosis of lymphoma in the vast majority of cases seen in clinical practice. Furthermore, in difficult cases or those with limited material or poor histology, immunophenotypic analysis may be the only means of making a definitive diagnosis.